ANALYSIS OF PLANNING IN THE MANAGEMENT OF ISLAMIC EDUCATIONAL INSTITUTIONS BASED ON THE QUR'AN AND HADITH - Li’anatuz Zuhro , Siti; Fauzi , Imam (Antis-Publisher, 2024)
Objective: This study aims to analyze the critical role of planning as a foundational aspect in Islamic education management and how its integration with organizing contributes to institutional success. Method: The research employs a literature review approach, involving problem formulation, collection of relevant articles, comparative analysis of research findings, data tabulation, and conclusion presentation. Results: The findings reveal that meticulous planning and effective organizing work synergistically to enhance the quality of Islamic education. This synergy significantly supports the development and sustainability of Islamic educational institutions. Novelty: This study highlights the integration of planning and organizing as interdependent management functions, providing fresh insights for practitioners in designing and managing Islamic educational institutions more effectively.